2022
DOI: 10.3389/fnagi.2022.892754
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Cortisol and Dehydroepiandrosterone Sulfate, Alzheimer’s Disease Pathology, and Cognitive Decline

Abstract: IntroductionElevated cortisol levels have been reported in Alzheimer’s disease (AD) and may accelerate the development of brain pathology and cognitive decline. Dehydroepiandrosterone sulfate (DHEAS) has anti-glucocorticoid effects and it may be involved in the AD pathophysiology.ObjectivesTo investigate associations of cerebrospinal fluid (CSF) cortisol and DHEAS levels with (1) cognitive performance at baseline; (2) CSF biomarkers of amyloid pathology (as assessed by CSF Aβ levels), neuronal injury (as asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Our findings suggest that the ratio of DHEAS to cortisol is one possible mechanism mediating cognitive changes in chimpanzees. In humans, a high cortisol to DHEAS ratio has been negatively correlated with hippocampal, amygdala, and insula volume in humans, and with tau and p-tau levels ( Jin et al, 2016 ; Ouanes et al, 2022 ). Although further research correlating brain volume and adrenal steroids in chimpanzees is needed to test whether this relationship is similar in chimpanzees and humans, a previous study that included the chimpanzees described in the present work found age-related loss in grey matter in brain regions associated with cognition, and old chimpanzees with greater grey matter performed better within their age category ( Mulholland et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that the ratio of DHEAS to cortisol is one possible mechanism mediating cognitive changes in chimpanzees. In humans, a high cortisol to DHEAS ratio has been negatively correlated with hippocampal, amygdala, and insula volume in humans, and with tau and p-tau levels ( Jin et al, 2016 ; Ouanes et al, 2022 ). Although further research correlating brain volume and adrenal steroids in chimpanzees is needed to test whether this relationship is similar in chimpanzees and humans, a previous study that included the chimpanzees described in the present work found age-related loss in grey matter in brain regions associated with cognition, and old chimpanzees with greater grey matter performed better within their age category ( Mulholland et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that DHEAS levels are affected by acute and chronic stress due to its antagonistic action on glucocorticoids ( Kalimi et al, 1994 ; Maninger et al, 2010 ; McNelis et al, 2013 ). For this reason, recent studies that adopted the co-measurement of cortisol and DHEAS to investigate cognition and stress levels in several species, including marine mammals ( Gundlach et al, 2018 ; O’Brien et al, 2017 ), ungulates ( Almeida et al, 2008 ; Jurkovich et al, 2020 ), humans ( DeBruin et al., 2002 ; Miller et al, 1998 ; Ouanes et al, 2022 ), and nonhuman primates ( Goncharova, Vengerin & Chigarova, 2012 ; Maninger et al, 2010 ; Takeshita et al, 2014 ; Takeshita et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also used a battery of cognitive tests to assess the most important cognitive domains (including episodic memory, verbal fluency, executive functions, and visuospatial construction) and proxy questionnaires to evaluate basic and instrumental activities of daily living, as previously described [ 5 ]. These tools are validated and widely used in the field.…”
Section: Methodsmentioning
confidence: 99%
“…NPS have been linked to poorer quality of life and to more pronounced impairment in activities of daily living [ 1 , 4 ]. Their presence has also been associated with faster disease progression and earlier institutionalization [ 2 , 5 ]. NPS, especially irritability, agitation, sleep disturbances, anxiety, apathy, and delusion, have also been shown to increase the caregiver burden [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation